Microwave photoconductance decay measurements of n- and p-type silicon irradiated with neutrons and protons. (August 2021) - Baek, Hani; Kwon, Gihyun; Nam, Jongsuk; Kim, Sangeun; Kim, Hyoungtaek; Park, Byung-Gun; Lee, Jungil; Kang, Minyong; Sun, Gwang Min; Shin, Chansun
Abstract: N-type and p-type silicon were irradiated by neutrons and protons from low to high fluence range (10 8 − 10 11 cm -2 for neutrons and 10 10 − 10 13 cm -2 for protons). The carrier recombination lifetime of each irradiated silicon was measured using a microwave photoconductance decay method, and the resistivity of the irradiated silicon was also measured. Both neutron and proton irradiation induced a similar lifetime at the same irradiation fluence. The defect formation rates were determined to vary with irradiation fluence from the inverse lifetime dependence on irradiation fluence. The sheet resistance was increased above a threshold fluence. The result shows that at least three different values of defect formation rate are present in the fluence range of 10 9 − 10 15 cm -2, and it may have potential for practical use as low-dose dosimeters. Highlights: Irradiation of Si wafers by neutrons and protons from low to high fluence range. Defect formation rates determined from the inverse carrier lifetimes dependence on irradiation fluence. Fluence-dependent lifetime changes of Si have strong potential for practical use.